Pengaruh Likuiditas, Profitabilitas, dan Leverage Terhadap Nilai Perusahaan dengan Kebijakan Dividen sebagai Variabel Mediasi - Ronaldo (Journal of Innovation in Management, Accounting and Business, 2025)
This study aims to analyze the effect of liquidity, profitability, and leverage on firm value, with dividend policy as a mediating variable, in food and beverage companies listed on the Indonesia Stock Exchange for the 2021–2023 period. Firm value is an important indicator in assessing a company's performance and prospects. Fundamental factors such as liquidity, profitability, and leverage can influence market perception, while dividend policy acts as a financial signal that can strengthen this relationship. This study uses a quantitative method with a Structural Equation Modeling – Partial Least Squares (SEM-PLS) approach. Liquidity variables are measured using Current Ratio (CR) Quick Ratio (QR), profitability using Return on Assets (ROA) Return on Equity (ROE) and Net Profit Margin (NPM), leverage using Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), dividend policy using Dividend Payout Ratio (DPR), Dividend Yield (DY), and company value using Price to Book Value (PBV) and TOBIN'S Q. The results of the study indicate that liquidity has a negative and significant effect on company value through dividend policy. Profitability has a positive but insignificant effect on company value either directly or through dividend policy. Meanwhile, leverage has a positive and significant effect on company value, including through dividend policy. These results emphasize the importance of managing financial structure and dividend policy as a strategy to increase company value.